Stakeholders' perception of the educational programmes for children with intellectual disability in Ogun and Lagos states, Nigeria (2012)
This paper discusses the stakeholders'perception of the educational programmes for children with intellectual disability in Ogun and Lagos States, Nigeria. Children with intellectual disability were deprived of educational programmes in the past. when compared with other categories of children with special needs. However,a few decades ago. children 'with intellectual disability' were included in the educational programme.This paper sought to identify the types of programmes that are in place for children with intellectual disability and to 'what extent they are effective.One hundred and thirty eight (138) special teachers from Ogun and Lagos states participated in the study. The instrument used in collecting data was the educational programmes for children with intellectual disability questionnaire(EPCIDQ). Data collected were analyysed using descrpitive statistics. Results revealed that segregation (special school) was the major form of educational programme being practiced, although mainstreaming and inclusive were said to be in practice by the teachers. However, shortage of trained teaachers was identified as the major constraints in the educational programmes in both Ogun and Lagos states. It was therefore recommended that the government should endevour to train more teachers as a matter of urgency for effectiveness in the education of children with intellectual disability. Main streaming and inclusive education should be much more in practice over segregation method as this is hoped that it will reduce or eliminate the discrimination of the society against children with disability.